Systematic review and meta-analysis of effectiveness of preoperative embolization in surgery for metastatic spine disease. (16th September 2017) - Luksanapruksa, Panya; Buchowski, Jacob M; Tongsai, Sasima; Singhatanadgige, Weerasak; Jennings, Jack W
Abstract : Background: Preoperative embolization (PE) may decrease intraoperative blood loss (IBL) in decompressive surgery of hypervascular spinal metastases. However, no consensus has been found in other metastases and no meta-analysis which reviewed the benefit of PE in spinal metastases has been conducted. Objective: To assess IBL in spinal metastases surgery in a randomized controlled trial (RCT) and cohort studies comparing PE and a control group of non-embolized patients. Methods: A systematic search of relevant publications in PubMed and EMBASE was undertaken. Inclusion criteria were RCTs and observational studies in patients with spinal metastases who underwent spine surgery and reported IBL. Meta-analysis was performed using standardized mean difference (SMD) and mean difference (MD) of IBL. Heterogeneity was assessed using the I 2 statistic. Results: A total of 265 abstracts (126 from PubMed and 139 from Embase) were identified through database searching. The reviewers selected six studies for qualitative synthesis and meta-analysis. The pooled SMD of the included studies was 0.58 (95% CI −0.10 to 1.25, p=0.09). Sensitivity analysis revealed that, if the study by Rehak et al was omitted, the pooled SMD was significantly changed to 0.88 (95% CI 0.39 to 1.36, p<0.001) and PE reduced the IBL significantly. The pooled MD was 708.3 mL (95% CI −224.4 to 1640.9 mL, p=0.14). If the results of the Rehak et al study were omitted, the pooled MD was significantly changed to 1226.9 mL (95% CI 345.8 to 2108.1 mL, p=0.006). Conclusions: PE can be effective in reducing IBL in spinal metastases surgery in both renal cell carcinoma and mixed primary tumor groups.